Early ovarian ageing: is a low number of oocytes harvested in young women associated with an earlier and increased risk of age-related diseases?. Issue 10 (19th September 2020) - Christensen, M W; Kesmodel, U S; Christensen, K; Kirkegaard, K; Ingerslev, H J
Abstract: STUDY QUESTION: Do young women with early ovarian ageing (EOA), defined as unexplained, and repeatedly few oocytes harvested in ART have an increased risk of age-related events? SUMMARY ANSWER: At follow-up, women with idiopathic EOA had an increased risk of age-related events compared to women with normal ovarian ageing (NOA). WHAT IS KNOWN ALREADY: Early and premature menopause is associated with an increased risk of cardiovascular diseases (CVDs), osteoporosis and death. In young women, repeated harvest of few oocytes in well-stimulated ART cycles is a likely predictor of advanced menopausal age and may thus serve as an early marker of accelerated general ageing. STUDY DESIGN, SIZE, DURATION: A register-based national, historical cohort study. Young women (≤37 years) having their first ART treatment in a public or private fertility clinic during the period 1995–2014 were divided into two groups depending on ovarian reserve status: EOA (n = 1222) and NOA (n = 16 385). Several national registers were applied to assess morbidity and mortality. PARTICIPANTS/MATERIALS, SETTING, METHODS: EOA was defined as ≤5 oocytes harvested in a minimum of two FSH-stimulated cycles and NOA as ≥8 oocytes in at least one cycle. Cases with known causes influencing the ovarian reserve (endometriosis, ovarian surgery, polycystic ovary syndrome, chemotherapy etc.) were excluded. To investigate for early signs of ageing, primary outcome was an overall risk of ageing-related events, defined as a diagnosis of either CVD, osteoporosis, type 2 diabetes, cancer, cataract, Alzheimer's or Parkinson's disease, by death of any-cause as well as a Charlson comorbidity index score of ≥1 or by registration of early retirement benefit. Cox regression models were used to assess the risk of these events. Exposure status was defined 1 year after the first ART cycle to assure reliable classification, and time-to-event was measured from that time point. MAIN RESULTS AND THE ROLE OF CHANCE: Median follow-up time from baseline to first event was 4.9 years (10/90 percentile 0.7/11.8) and 6.4 years (1.1/13.3) in the EOA and NOA group, respectively. Women with EOA had an increased risk of ageing-related events when compared to women with a normal oocyte yield (adjusted hazard ratio 1.24, 95% CI 1.08 to 1.43). Stratifying on categories, the EOA group had a significantly increased risk for CVD (1.44, 1.19 to 1.75) and osteoporosis (2.45, 1.59 to 3.90). Charlson comorbidity index (1.15, 0.93 to 1.41) and early retirement benefit (1.21, 0.80 to 1.83) was also increased, although not reaching statistical significance. LIMITATIONS, REASONS FOR CAUTION: Cycles never reaching oocyte aspiration were left out of account in the inclusion process and we may therefore have missed women with the most severe forms of EOA. We had no information on the total doses of gonadotrophin administered in each cycle. WIDER IMPLICATIONS OF THE FINDINGS: These findings indicate that oocyte yield may serve as marker of later accelerated ageing when, unexpectedly, repeatedly few oocytes are harvested in young women. Counselling on life-style factors as a prophylactic effort against cardiovascular and other age-related diseases may be essential for this group of women. STUDY FUNDING/COMPETING INTEREST(S): No external funding was received for this study. All authors declare no conflict of interest. TRIAL REGISTRATION NUMBER: N/A